High Nature Value Farming Systems classification: A landscape-based approach - Almeida, Mara (2013)
The High Nature Value (HNV) classification of farm systems, proposed by the European Environment Agency, emerges as more relevant todaycentral in the preparation of the rural development programmenegotiation of the agri-environment and rural areas supportwithin the, on the CAP post-2013. HNV classification is applicable across all Europe and seeks to define objective criteria for identifying farm systems who support high biodiversity values and landscape quality, what may also be linked to other ecosystem servicesthe farming system functioning and for the ecosystem services associated with it. Considering that changes in rural space, taking place across all Europe, have been occurring at different levels, paces and intensities, the assessment of HNV farming needs also to take account of this differentiation., Sconsidering spatially based approaches at the regional level, linked to landscape based indicators, may be the way forward to eliable information, required for t, is needed in order to meet the contemporary rural policy making. The Alentejo region is a wide territory with a complex reality. There are several types of farming systems in different natural conditions (soils, climate, and topography) and in different management contexts over time. Today in Alentejo, extensive farming activities are of great relevance and have a great impact on vegetation composition, species distribution and landscape pattern and consequently they influence landscape quality and attractiveness and also conditions for recreational activities. This close relationship between farming practices and landscape patterns led us to seek what defines a HNV farming system in Alentejo context and to identify its distribution considering landscape as the basis for a spatial approach. Recognizing the diversity of farming system types, according to geographical distribution, biophysical context and farm structure, the aim is to identify the landscape patterns associated with different farming system types and to relate them with the HNV classification in order to define landscape indicators for this classification. The proposed presentation will focus on the methodological approach and the consequent development of the landscape based HNV indicators, applicable to Alentejo.